'Sticky' foods: How school practices produce negative emotions for mothers and children. (November 2019) - Tanner, Claire; Maher, JaneMaree; Leahy, Deana; Lindsay, Jo; Supski, Sian; Wright, Jan
Abstract: This paper addresses health messages that are carried home from school – a space where childhood obesity prevention measures are being transmitted to families, and mothers in particular. We consider what emotions are being produced for mothers and children in the enactment of current school health initiatives, especially those aimed at 'improving' family food practices. Our analysis draws on interviews with parents and primary-school-aged children (n = 50) in Australia collected as part of a project on children's role as health advocates in family contexts. Using Sara Ahmed's work on emotions and John Law's concept of 'collateral realities', we consider how clashes and confrontations in 'healthy' food practices between home and school are producing negative emotions for mothers and children. We argue that rigid school rules and their policing at school, while aimed at promoting health, are producing unintended negative affects for families and children. We conclude by offering some recommendations on how more inclusive school health promotion practices can enable and support, rather than harm, the emotional well-being of mothers and children. Highlights: Analyses the emotional effects of school health promotion practices. Incorporates theories of Sara Ahmed and John Law. Shows that rigid school food rules produce negative emotions for families. Argues that more inclusive school health practices are needed to support the emotional well-being of mothers and children.